One step derivatization and preconcentration microextraction technique for determination of bisphenol A in beverage samples by gas chromatography-mass spectrometry - Fontana, Ariel Ramón (2011)
A simple technique based on ultrasound-assisted emulsification microextraction in-situ derivatization (USAEME-ISD) is proposed for the one step derivatization, extraction and preconcentration of bisphenol A (BPA) in beverages samples prior to gas chromatography-mass spectrometry (GC-MS) analysis. BPA was in-situ derivatized with acetic anhydride and simultaneously extracted and preconcentrated by using USAEME. Variables affecting the extraction efficiency of BPA were evaluated. Under optimal experimental conditions, the detection limit (LOD) was 38 ng L-1 with a relative standard deviation (RSD) value of 11.6 %. The linear working range was 100-1250 ng g-1 the coefficient of estimation (r2) of the calibration curve was higher than 0.9971. The robustness of the proposed methodology was probed by developing a recovery study at two concentrations (125 and 500 ng L-1) over different beverages samples. This study led to a satisfactory result achieving recoveries higher than 82 % showed a successfully robustness for determination of BPA in samples of food safety interest.